Pemberian Kompos Jerami dan Tepung Cangkang Telur pada Tanaman Kangkung di Desa Mallinrung Kec. Libureng Kab. Bone Provinsi Sulawesi Selatan - Muhammad Nur Ichwan; Sutoyo Sutoyo; Eny Wahyuning Purwanti (bionature, 2021)
Abstract. This study was to determine the type of organic fertilizer treatment that can give the best results on kale plants. The independent sample t-test was used to compare the two types of organic fertilizer treatments. The treatments include straw compost and eggshell flour with each treatment being repeated 30 times. The dose of fertilizer used was 26.810 g for each kale plant. The results showed that there was no significant difference between the two treatments of organic fertilizers which were given both straw compost and eggshell flour with a dose of 26.810 g on the parameters of the observation of fresh harvest weight and power save plant.Keywords: straw compost, eggshell flour, kale plants